Pathways of empowerment perceptions, health literacy, self-efficacy, and self-care behaviors to glycemic control in patients with type 2 diabetes mellitus. Issue 2 (February 2016) - Lee, Yau-Jiunn; Shin, Shyi-Jang; Wang, Ruey-Hsia; Lin, Kun-Der; Lee, Yu-Li; Wang, Yi-Hsien
Highlights: Health literacy indirectly affected self-care behaviors through the mediation of self-efficacy. Enhancing health literacy can be a potential strategy for improving self-efficacy. Empowerment approach can be a potential strategy for improving health literacy. Abstract: Objective: To validate a hypothesized model exploring the influencing pathways of empowerment perceptions, health literacy, self-efficacy, and self-care behaviors to glycosylated hemoglobin (HbA1c) levels in patients with type 2 diabetes (T2DM). Methods: Overall, 295 patients with T2DM were recruited from five endocrine clinics in Taiwan through convenience sampling. Data regarding personal characteristics, empowerment perceptions, health literacy, self-efficacy, self-care behaviors, and HbA1c levels were collected. A structural equation modeling was used to validate the hypothesized model. Results: Significant direct pathways were determined from empowerment perceptions to health literacy, from health literacy to self-efficacy, from self-efficacy to self-care behaviors, and from self-care behaviors to HbA1c levels. Conclusions: The empowerment perceptions and health literacy relatively influenced self-efficacy and self-care behaviors. Self-efficacy and self-care behaviors relatively influenced glycemic control in patients with T2DM. Practice implications: Modifying self-care behaviors have been demonstrated to be the most essential for improving glycemic control. To improve self-care behaviors, healthcare providers should target improving self-efficacy, and enhancing health literacy can be considered to be a potential strategy for improving self-efficacy. To enhance health literacy, healthcare providers could use an empowerment approach rather than an authoritative approach that emphasizes patient compliance in managing patients with T2DM.